Pengaruh Ukuran Perusahaan, Audit Tenur, Dan Pertumbuhan Perusahaan Terhadap Opini Audit Going Concern - Al’adawiah, Rubiyah; Julianto, Wisnu; Sari, Retna (Institut Bisnis dan Informatika Kesatuan, 2020)
This study was conducted to determine the effect of the variable Company Size, Tenure Audit, and Company Growth on Going Concern Audit Opinions on trade, service and investment sector companies listed on the Indonesia Stock Exchange in the 2014-2018 period. The data used in this research are secondary data. The sample used in this study amounted to 104 companies using a purposive sampling method. The analysis technique used is logistic regression. At a significance level of 5%, the results of this study indicate that the Company Size variable and the Company Growth variable influence the Going Concern Audit Opinion. While the Audit Tenure variable does not affect the Going Concern Audit Opinion. Keywords : Going Concern Audit Opinion, Company Size, Tenur Audit, Company Growth